HUKUM TRANSEKSUAL DAN KEDUDUKAN HUKUM PELAKUNYA DALAM KEWARISAN ISLAM - Suhairi Suhairi (Nizham Jurnal Studi Keislaman, 2016)
This research explains about transsexual and its position in Islamic inheritance. Transsexual included in gender identity disorders. The main characteristic of this problem is the mismatch between the genitals and gender identity. Gender identity is the feeling of a person belonging to a particular gender, in other words the realization that he is male or female. The law of transsexual (genital surgery) is absolutely haram. Whereas, genital operation in order to enchantment/improvement of double genital or abnormality, is permissible even encouraged in Islam. The law position of transsexual offender (sex change) toward normal genital is not change, remains theirs before surgery. Woman who does transsexual as men, then the legal position in Islamic inheritance remained as a woman, so are the men. Meanwhile for the perpetrators of gender surgery in order to improve / repair the double genitalia or genitalia that is not perfect, the legal position in the Islamic inheritance according to the sex of the operating results.